THE INFLUENCE OF Ustadz YOUTUBiyah ON THE EXPRESSION OF RELIGIOUS AMONG MILLENNIAL MUSLIM ADOLESCENT - Hastuti Hastuti; Titi Mildawati Titi Mildawati; Moh. Tajuddin Moh. Tajuddin (Jurnal Teknologi Pendidikan Madrasah, 2022)
One social media platform with the most users in Indonesia is YouTube. YouTube is an effective and efficient medium for disseminating information because it has exclusive features compared to other platforms. So, YouTube is the most appropriate medium for communicating data in today's era, including spreading da'wah. Many ustadz use YouTube as a place to convey the teachings of Islam, so the term Ustadz YouTubiyah was born among millennial Muslim teenagers. Teenagers, as YouTube users, are mostly connoisseurs of Islamic content. The fanaticism towards the ustadz who is idolized affects their perspective and critical thinking, even to the point of following the style of the worshiped ustadz. The outlook on religious teachings conveyed by Ustadz YouTubiyah, in the expression of adolescent religious behavior following the character of Ustadz YouTubiyah's preaching, was engaging. Therefore, this research was conducted with a quantitative type which became the research location at the Faculty of Science and Technology UIN Alauddin Makassar to analyze forms of religious expression in students of the Faculty of Science and Technology UIN Alauddin Makassar in 2021 and to find out whether Ustadz YouTubiyah influenced these expressions? From the results of the study, it was found that the religious expression/behavior of the students of the Faculty of Science and Technology varied; in terms of clothing, some were passionate with a closed appearance, and on the contrary, some were modest, and some even appeared free (not following the rules of the faculty/religious law). This diversity of expressions is largely influenced by the habit of watching Islamic content of the ustadz on YouTube. So the conclusion of this study is that Ustadz YouTubiyah has an effect on religious expression among millennial teenagers.